Design Optimization and Analysis of Radial Flux Permanent Magnet Generator Using Local Optimization Method - Mostaman, Nur Afiqah; Sulaiman, Erwan; Jenal, Mahyuzie (ECJSE, 2023)
Recently, Permanent Magnet Generator has been widely used due to its ability to have simple structure yet high efficiency. To maximize the output performance of the generator advances and trends in mathematical modelling and computer simulation using optimization techniques have opened the way to a new approach to electrical machine design. In this paper, a Radial Flux Permanent Magnet Generator (RFPMG) configuration was examined and optimized throughout sizes and weight using the Local Optimization Method as an iterative process in order to achieve optimal output. By utilizing the LOM technique as an optimization process, the output voltage of RFPMG increased by 13.64% from the initial results. With a corresponding increase in output voltage performances, the configuration geometry adjustment additionally helps in expanding the generator’s operational area. Hence, this paper presents the contributions of advancement resulting in an increment of the back-electromotive force value and with the reduction in the permanent magnet volume after the optimization process.